Distance learning succeeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Two years; ago, Wye College (University of London) broke new ground by offering a Distance Learning Masters Programme in Agricultural Development (see Course Announcements', Spore 27). Two hundred and fifty students from 70 countries have so far...